Physical Activity Elements and Adverse Outcomes in Patients with Chronic Kidney Disease in Guangdong (PEAKING) project: protocol for a prospective cohort study - Hui Liu; Qian Wang; La Zhang; Xindong Qin; Xusheng Liu; Jianfeng Wu; Yifan Wu; Changyuan Yang; Ruolan Duan; Zhenhua Yang; Jiamei Qiu; Minhui Pi; et al. (BMJ Open)
Introduction Physical inactivity is prevalent and associated with adverse outcomes among patients with chronic kidney disease (CKD). Most previous studies have relied on subjective questionnaires to assess levels of physical activity (PA) and mainly focused on patients undergoing dialysis. Therefore, the Physical Activity Elements and Adverse Outcomes in Patients with Chronic Kidney Disease in Guangdong study aims to investigate the levels and types of PA elements and their association with adverse outcomes in Chinese non-dialysis CKD (ND-CKD) patients.Methods and analysis In this prospective cohort study, 374 patients with ND-CKD will be recruited from Guangdong province, South of China. The primary exposure will be levels of PA assessed by ActiGraph GT3X+ accelerometer including the intensity, duration, frequency and type of PA. The traditional Chinese exercises such as tai chi and Baduanjin will also be assessed. The primary outcomes will be all-cause mortality. Other variables including demographics, comorbidities, medication and laboratory markers will be registered. All data will be updated annually for at least 5 years, or until the occurrence of death or initiation of renal replacement therapy. The Spearman correlation coefficient will be used to investigate the correlation between questionnaire-derived and accelerometry-derived PA. The Cox proportional hazards model will be used to investigate the association between level of PA and adverse outcomes. Non-linear associations between PA levels and outcomes, as well as the minimum desirable PA level, will be evaluated using restricted cubic splines.Ethics and dissemination The ethical permission for this study was obtained from the ethics committee of Guangdong Provincial Hospital of Chinese Medicine in Guangzhou, China (B2015-152-02). Written informed consent is obtained from all participants. The results will be disseminated by publication in a peer-reviewed journal and presented at relevant conferences.